Numerical study on the aerodynamic performance of dragonfly (Anax parthenope julius) maneuvering flight during synchronized-stroking (Physics of fluids (1994), 2024)
Dragonflies exhibit outstanding performance in flight due to their exceptional flying capabilities. However, micro air vehicles developed based on biomimetics principles fall far short of dragonflies in terms of maneuverability. To investigate the ability of dragonflies to change flight states per unit time during synchronized-stroking, this study first takes the dragonfly as the biological observation subject. Based on the acquired biological characteristics, a geometric model required for numerical simulation is established. Combined with the dynamic observation results and flapping patterns of the dragonfly, a systematic analysis of the aerodynamic performance and surrounding flow field structure during maneuvering flight at different flapping frequencies is conducted. The results indicate that changes in the dragonfly's flapping frequency have a significant impact on lift and roll moment, while the impact on pitch moment and lateral force is minimal, varying only within the range of 10%–20% with a frequency increase in 5 Hz. Even with the same flapping frequency in the left and right wings, a residual pitch moment of up to 18.5 mN mm remains, causing the dragonfly's body to oscillate back and forth. By changing the flapping frequency of one wing, the dragonfly can achieve maneuvering turns to the opposite side. During the entire downstroke, the fluid around the wings generates additional circulation due to rotational effects, which is more beneficial for maneuvering takeoff. During the upstroke, the trailing-edge vortices shed significantly, creating a large pressure difference between the forewing and hindwing surfaces, which is more conducive to forward maneuvering flight.